2020
DOI: 10.1002/agj2.20408
|View full text |Cite
|
Sign up to set email alerts
|

Oilseed rape straw returning changes soil reducibility and affects the root and yield of rice in the rape‐rice rotation field at Sichuan Basin area of China

Abstract: To elucidate the influence of rape straw returning on soil reducibility and to understand its effects on rice growth and yield in rape-rice rotation system, 3 years field experiment with 8 treatments of straw incorporation carried out at Mianyang Sichuan Province of China. Results showed that the lowest RC Eh value founded at 14-18 d after rice planting; With the increasing of rape straw incorporation, the amount of root (number, weight and length) and root bleeding intensity both increased significantly durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Straw returning is an effective way to improve soil properties and fertility. Many studies have shown that straw returning can improve the soil nutrient content and promote the uptake of soil nitrogen by roots, thus increasing the rice yield, and the yield increases with the increase of straw returning years ( Wang et al., 2020 ; Cui et al., 2022 ). However, some studies held that straw returning has no significant effect on rice yield and even has a tendency to reduce it, which is related to soil texture and tillage methods ( Zhu et al., 2011 ; Zhang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Straw returning is an effective way to improve soil properties and fertility. Many studies have shown that straw returning can improve the soil nutrient content and promote the uptake of soil nitrogen by roots, thus increasing the rice yield, and the yield increases with the increase of straw returning years ( Wang et al., 2020 ; Cui et al., 2022 ). However, some studies held that straw returning has no significant effect on rice yield and even has a tendency to reduce it, which is related to soil texture and tillage methods ( Zhu et al., 2011 ; Zhang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 1999); (2) reducing soil oxygen content and consequently inhibiting the growth and development of rice roots (Wang et al ., 2019); and (3) producing reducing substances that have toxic effects on rice roots (Wang et al. , 2020). These possible contributing factors highlight the need for a fundamental understanding of the effects of fallow weed decomposition on soil biological and chemical properties in rice paddies.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the application of fallow weeds reduced aboveground N uptake and biomass production during the early growth period (from transplanting to MT) in rice. This could be attributable to decomposition of fallow weeds (1) stimulating immobilization of N by soil microorganisms, resulting in N competition between soil microorganisms and rice roots (Cheshire et al, 1999); (2) reducing soil oxygen content and consequently inhibiting the growth and development of rice roots (Wang et al, 2019); and (3) producing reducing substances that have toxic effects on rice roots (Wang et al, 2020). These possible contributing factors highlight the need for a fundamental understanding of the effects of fallow weed decomposition on soil biological and chemical properties in rice paddies.…”
Section: Discussionmentioning
confidence: 99%
“…Mianyang (104.73°E, 31.47°N), located at the middle and upper reaches of the Fujiang River (Wang et al, 2020), has a typical subtropical monsoon climate, with an average annual temperature of 14.7-17.3 ℃ and average annual precipitation of 826-1417 mm. Its soil is typical clay-loam soil, with a bulk density of 1.29 g/cm 3 and organic matter content of 28.6 g/kg; its total nitrogen content is 1.68 g/kg, the total phosphorus is 0.37 g/kg, and the total potassium is 1.86 g/ kg, in 0-50 cm soil.…”
Section: Study Areamentioning
confidence: 99%